2006
DOI: 10.2353/jmoldx.2006.060089
|View full text |Cite
|
Sign up to set email alerts
|

Allele-Specific Polymerase Chain Reaction for the Imatinib-Resistant KIT D816V and D816F Mutations in Mastocytosis and Acute Myelogenous Leukemia

Abstract: Oncogenic mutations of the receptor tyrosine kinase KIT contribute to the pathogenesis of gastrointestinal stromal tumors , systemic mastocytosis (SM) , and some cases of acute myelogenous leukemia (AML). The D816V substitution in the activation loop of KIT results in relative resistance to the kinase inhibitor imatinib (Gleevec). Because this mutation occurs in 80 to 95% of adult SM , its detection has diagnostic and predictive significance. Unfortunately , the fraction of mutation-positive cells in clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 46 publications
(46 reference statements)
0
28
0
Order By: Relevance
“…However, patients with C-KIT/TKD frequently occur resistance to these drugs [Corless et al, 2006;Kosmider et al, 2007;Piccaluga et al, 2007;Verstovsek et al, 2008;Chevallier et al, 2009;Ustun et al, 2009]. Herein we show that FTY720 can induce toxic effects in both primary leukemic cells from AML patients and the AML cell lines harboring C-KIT/TKD or C-KIT/ WT.…”
mentioning
confidence: 88%
“…However, patients with C-KIT/TKD frequently occur resistance to these drugs [Corless et al, 2006;Kosmider et al, 2007;Piccaluga et al, 2007;Verstovsek et al, 2008;Chevallier et al, 2009;Ustun et al, 2009]. Herein we show that FTY720 can induce toxic effects in both primary leukemic cells from AML patients and the AML cell lines harboring C-KIT/TKD or C-KIT/ WT.…”
mentioning
confidence: 88%
“…Büttner et al [7] detected a codon 816 mutation in 6 of 6, Longley et al [8] detected D816V in 11 of 11, Yanagihori et al [9] detected a codon 816 mutation in 4 of 4, and Garcia-Montero et al [3] detected a D816V mutation in 10 of 10 adult cases of sporadic SM. However, several studies have also reported significant proportions of KIT codon 816 mutation-negative skin biopsies from adult sporadic mastocytosis, including Verzijl et al [16] and Corless et al [17] where 5 of 8 and 9 of 13 cases, respectively, were tested mutation-negative. The cases testing mutation-negative in skin had not been confirmed mutation-positive in other tissues.…”
Section: Resultsmentioning
confidence: 99%
“…However, with the known high fraction of mutation-positive adults with mastocytosis, most of these cases were likely to carry the mutation but tested negative due to insufficient analytical sensitivity [16]. The allele-specific PCR used by Corless et al [17] was reported to detect 1% mutation-positive alleles (= 2% mutation-positive cells) in formalin-fixed paraffin-embedded derived DNA as used in the study, and should, based on the present results, be expected to reliably detect the mutation in most cases. However, it is possible that the analytical sensitivity has been reduced below the expected value due to limiting amounts of amplifiable template DNA, which is a known problem with formalin-fixed paraffin-embedded skin and commonly observed in our laboratory [T. Kristensen, unpubl.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9][10] Myelomastocytic leukemia is distinct from SM with associated clonal hematologic nonemast cell lineage disease (SM-AHNMD), mast cell leukemia, and AML with tryptase expression, KIT (v-kit Hardy-Zuckerman 4 feline sarcoma viral oncogene homolog; c-KIT gene) mutation at codon 816, or both. 5,[11][12][13][14][15][16] This report presents a patient with myelomastocytic leukemia that had aberrant CD25 expression. It describes the clinicopathologic features of this patient and provides a focused review of the literature on this rare variant of AML.…”
Section: Introductionmentioning
confidence: 99%